2023
DOI: 10.1088/1742-5468/acb262
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement and negativity Hamiltonians for the massless Dirac field on the half line

Abstract: We study the ground-state entanglement Hamiltonian of several disjoint intervals for the massless Dirac fermion on the half-line. Its structure consists of a local part and a bi-local term that couples each point to another one in each other interval. The bi-local operator can be either diagonal or mixed in the fermionic chiralities and it is sensitive to the boundary conditions. The knowledge of such entanglement Hamiltonian is the starting point to evaluate the negativity Hamiltonian, i.e. the logarithm of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Other possible extensions to consider are non-vanishing temperature for the entire system, or a non-vanishing mass [105], or a subsystem made by the union of a generic number of disjoint intervals [51,56,65], or spatially inhomogeneous backgrounds [66,67,106], or defects [107][108][109][110].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other possible extensions to consider are non-vanishing temperature for the entire system, or a non-vanishing mass [105], or a subsystem made by the union of a generic number of disjoint intervals [51,56,65], or spatially inhomogeneous backgrounds [66,67,106], or defects [107][108][109][110].…”
Section: Discussionmentioning
confidence: 99%
“…However, for n > 2 very few results are available in the literature. The case of an interval for the free massless Dirac field on the half line, which is the prototypical fermionic BCFT with c = 1, has been analyzed in [63] (see [64] for a lattice computation) and later extended to an arbitrary number of intervals [65].…”
Section: Introductionmentioning
confidence: 99%
“…Other choices correspond to Lifshitz-like dispersions ω ∼ p 1+α . We leave the exploration of such networks, their entanglement properties, whether the operator algebra is of type I or type III, and the connection to recent work in [12] to future work. Note that the ERG formalism discussed here can accommodate any Gaussian theory, including theories with no local actions such as generalized free fields (GFF).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Here we will take K 0 to be a function of zp/M and p/µ for some new intermediate scale µ. The transformation in (12) then remains a symmetry of the action and we can repeat the previous ERG construction. To summarize, we consider…”
Section: Non-relativistic Flowsmentioning
confidence: 99%
“…In [94][95][96] it was shown that in order to recover the CFT entanglement temperature β(x) in equation ( 5), it is necessary to perform a careful continuum limit which takes into account all of these higher contributions. This limiting procedure has allowed to reconstruct the CFT EH in many systems at criticality, both at finite temperature and in the ground state [94][95][96] and also in the presence of boundaries [95][96][97], in inhomogeneous and out-of-equilibrium systems [98,99] and in higher dimensions [100]. In [97,101] it has also been extended to the recently introduced negativity Hamiltonian [102], i.e.…”
Section: J Stat Mech (2024) 063102mentioning
confidence: 99%